Towards a general model for automatic and flexible design of closed wind tunnels - Prada y Nogueira, Isaac; Cuadra García, Fernando; Sánchez Miralles, Alvaro (My University, 2016)
Wind tunnels for aerodynamic testing of any kind are nowadays pre-designed on a trial and error basis, using the designer’s experience. Thereafter the designs are computer simulated using Computational Fluid Dynamics (CFD). This paper is a first stepping stone towards a general methodology for an automatic, flexible and optimized design of closed wind tunnels. The final aim is to yield better pre-designs which the designer can subsequently fine-tune with more detailed CFD analyses. The key objective and contribution of this paper is to present a complete set of truly independent variables and attributes, able to represent most closed tunnel configurations, including fan and cooling systems, and which allow for the application of advanced computer optimization methods. The proposed variable definition will be validated with representative tunnel designs and its contribution to the current state of the art will be shown with comparative CFD results on different tunnel families.

Wind tunnels for aerodynamic testing of any kind are nowadays pre-designed on a trial and error basis, using the designer’s experience. Thereafter the designs are computer simulated using Computational Fluid Dynamics (CFD). This paper is a first stepping stone towards a general methodology for an automatic, flexible and optimized design of closed wind tunnels. The final aim is to yield better pre-designs which the designer can subsequently fine-tune with more detailed CFD analyses. The key objective and contribution of this paper is to present a complete set of truly independent variables and attributes, able to represent most closed tunnel configurations, including fan and cooling systems, and which allow for the application of advanced computer optimization methods. The proposed variable definition will be validated with representative tunnel designs and its contribution to the current state of the art will be shown with comparative CFD results on different tunnel families.